2008
DOI: 10.1073/pnas.0811680106
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone-releasing hormone as an agonist of the ghrelin receptor GHS-R1a

Abstract: Ghrelin synergizes with growth hormone-releasing hormone (GHRH) to potentiate growth hormone (GH) response through a mechanism not yet fully characterized. This study was conducted to analyze the role of GHRH as a potential ligand of the ghrelin receptor, GHS-R1a. The results show that hGHRH(1-29)NH 2 (GHRH) induces a dose-dependent calcium mobilization in HEK 293 cells stably transfected with GHS-R1a an effect not observed in wildtype HEK 293 cells. This calcium rise is also observed using the GHRH receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 44 publications
3
18
0
Order By: Relevance
“…In this sense, it has been suggested that GOAT is located in the membrane of the ER and mediates the translocation of the octanoyl-CoA from the cytosolic side to the ER lumen prior to the transport of acylated ghrelin to the Golgi [31][32][33]. The subcellular localisation of ghrelin and GOAT found in the present study is similar to that observed in human myometrial smooth muscle cells and in the human embryonic kidney (HEK) 293 cell line [9,[34][35][36]. Further investigation is warranted to ascertain the mechanisms of ghrelin trafficking in human adipocytes.…”
Section: Discussionsupporting
confidence: 86%
“…In this sense, it has been suggested that GOAT is located in the membrane of the ER and mediates the translocation of the octanoyl-CoA from the cytosolic side to the ER lumen prior to the transport of acylated ghrelin to the Golgi [31][32][33]. The subcellular localisation of ghrelin and GOAT found in the present study is similar to that observed in human myometrial smooth muscle cells and in the human embryonic kidney (HEK) 293 cell line [9,[34][35][36]. Further investigation is warranted to ascertain the mechanisms of ghrelin trafficking in human adipocytes.…”
Section: Discussionsupporting
confidence: 86%
“…GH synthesis and secretion are induced by hypothalamic GHRH and gut-derived ghrelin. GHRH may also act as a coagonist for the ghrelin receptor (28). Hypothalamic SRIF suppresses GH secretion mainly by highaffinity binding to SSTR2 and SSTR5 receptor subtypes expressed on somatotrophs (90).…”
Section: Figurementioning
confidence: 99%
“…Just recently, interactions between the ghrelin and the GHRH-signaling pathway have been observed. Casanueva et al (2008) reported that the ghrelin GHS-R1a receptor can be activated by GHRH. Moreover, they discovered that GHRH appears to be an allosteric enhancer of ghrelin action.…”
Section: Ghrelin Effectsmentioning
confidence: 99%